How justify is my take home pay? - Nwanesi Peter, Karubi; Muhammad, Khalique (Universiti Malaysia Sarawak, (UNIMAS), 2011)
That Malaysia is one of the highest employers of migrant workers in Asia is no longer a debatable issue but a fact supported by overwhelming statistics. Penang one of the ever dynamic industrial regions of Malaysia provides work for thousands of young women from local and international countries. Most of these young women earns as little as RM450 per month and spend close to 45 working hours weekly. Most of these young women are as young as 18 years, doing jobs that have no bearing to their future career development. This and other factors have continued to strengthen most female factory workers to constantly be on a look out for a new industrial unit to sell their labour. In many instances, their toil is mechanical; devoid of emotion, attachment, and sometime commitment or loyalty to their job; after aIL they are being used and not appropriately compensated or cared for.